IOT-based safety alarm system in laboratory / Muhammad Shamizal Samsul Kamal - Samsul Kamal, Muhammad Shamizal (2024)
This safety alarm system in laboratory is an important aspect in detecting the source of danger and warn people through visual and audio appliances when smoke, fire, carbon monoxide or other emergencies are present. This project aims to design an IoT-based safety alarm system in laboratory using Arduino UNO as microcontroller. The input sensors that were utilized are MQ-2 gas sensor, DS18B20 temperature sensor and LM393 fire sensor. The sensors are used to detect dangerous elements that might harm the people in laboratory. Meanwhile, the outputs employ of three LEDs, buzzer, lcd display and remote monitor. The system would alert the user as the sensors detects the presence of danger in laboratory.